Evaluation of Prostate Specific Antigen Density and Transrectal Ultrasonography-Guided Biopsies in 100 Consecutive Patients with a Negative Digital Rectal Examination and Intermediate Serum Prostate Specific Antigen Levels - (:unkn) unknown (Blackwell Publishing, 1997)
Background: This study was undertaken to assess the importance of prostate biopsies in patients with a negative digital rectal examination (DRE) and elevated prostate specific antigen (PSA) levels and to investigate the role of PSA density (PSAD) and hypoechoic lesions on transrectal ultrasound (TRUS) in increasing the diagnostic sensitivity and specificity for prostate cancer (PCa). Methods: One hundred patients with varied initial symptoms who had a negative DRE and a PSA level between 4 and 20ng/mL underwent TRUS-guided systematic and, if present, lesion-directed biopsies. Results: PCa was detected in 11 patients (11%). TRUS examinations revealed hypoechoic lesions in 31 patients. Lesion-directed biopsies revealed PCa in 13% (4/31) of patients with abnormal TRUS whereas, 7% (5/69) of patients with negative TRUS findings had PCa. Additional systematic biopsies detected PCa in 2 patients where lesion-directed biopsies were negative. None (0/19) of the lesions smaller than 0.2 mL on TRUS had PCa whereas, 33% (4/12) of patients with lesions greater than 0.2 mL had PCa. When the subgroup of patients with negative TRUS and PSA levels between 4 and 10ng/mL were considered, 25% (1/4) of cases with PCa would have been missed if 0.15 was used as the cut-off point for PSAD, however, this would save 61% (30/49) of unnecessary biopsies. The positive predictive value of PSA (cut-off level 10ng/mL), PSAD (cut-off level 0.15), and hypoechoic lesions on TRUS were found to be 11.5%, 33%, and 13%, respectively. When hypoechoic lesions greater than 0.2mL were taken as the positive finding, the positive predictive value and specificity rates of TRUS increased to 33% and 91%, respectively, without any change in the sensitivity. Conclusions: In patients with a negative DRE and intermediate PSA levels, the application of PSAD would have saved 49% of study patients with BPH from a biopsy, but would have missed 27% of PCa cases. By ignoring lesions smaller than 0.2 mL on TRUS, a very high specificity of 91% was achieved with a sensitivity of 36%. Thus, further investigations aimed at defining a better mode of diagnosis of PCa are warranted.
Keywords: Early diagnosis; Prostate neoplasm; PSA; TRUS